Serbia and Montenegro : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that macroeconomic imbalances in Serbia and Montenegro widened in 2004, putting at risk some of the impressive earlier achievements. Growth, about 5 percent in nonagriculture since 2002, has been fueled by a surge in domestic demand. Lack of competitive domestic production has led to increased imports and a widening current account deficit. The main policy challenge is to maintain macroeconomic stability while accelerating structural reform. Fiscal policy needs to be tightened substantially, and its flexibility increased by reducing the large share of nondiscretionary spending.